2009
DOI: 10.1002/j.2050-0416.2009.tb00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Hull-less Barley Malt for Use in Malt and Grain Whisky Production

Abstract: Hull‐less (or husk‐less) barley is possibly one of the most important developments in barley in recent years. This study looked at the potential of hull‐less barley for use by the Scotch whisky industry. By modifying the malting conditions for hull‐less barley, it was possible to provide good alcohol yield as well as significant improvements in processing characteristics. The biochemistry controlling the germination of hull‐less barley was consistent with established knowledge about ‘normal’ hulled barley exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 7 publications
1
26
0
9
Order By: Relevance
“…In addition, as this work was set up to compare the hull-less lines with Optic, a similar malting regime to that of Agu et al 3 was used. Agu et al 4 have subsequently shown that hull-less barley can malt successfully after a much shorter steeping period, so future work will also consider cell wall modification and wort filtration, in the context of malting regimes that require lower inputs of water and energy. Wort filtration rates were not quantified in this experiment as no obvious problems were observed with any of the hull-less samples, probably due to the high levels of cell wall modification that had generally occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as this work was set up to compare the hull-less lines with Optic, a similar malting regime to that of Agu et al 3 was used. Agu et al 4 have subsequently shown that hull-less barley can malt successfully after a much shorter steeping period, so future work will also consider cell wall modification and wort filtration, in the context of malting regimes that require lower inputs of water and energy. Wort filtration rates were not quantified in this experiment as no obvious problems were observed with any of the hull-less samples, probably due to the high levels of cell wall modification that had generally occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of mash filters, which effectively squeeze out the wort, provide a solution for modern, large-scale breweries, but are not viable for malt distilling, which traditionally relies on large numbers of relatively small-scale production units. The extent to which filtration problems result from an absence of husk has, however, been questioned by recent research, within the distilling industry, as Agu et al 3,4 suggested that the extent of modification may be at least as important in ensuring rapid filtration.…”
Section: Introductionmentioning
confidence: 99%
“…Buck is also suitable for malt, beer, and whiskey production under specialized conditions, given its potential to have high malt extract percentage. Naked barley absorbs water more rapidly that covered barley, which can reduce malting time, energy, and water needs (Agu et al, 2009). The hull accounts for approximately 11 to 13% of the grain weight but does not contribute to starch content; therefore, naked barleys have a much higher potential alcohol content than covered barleys (Agu et al, 2009).…”
mentioning
confidence: 99%
“…Naked barley absorbs water more rapidly that covered barley, which can reduce malting time, energy, and water needs (Agu et al, 2009). The hull accounts for approximately 11 to 13% of the grain weight but does not contribute to starch content; therefore, naked barleys have a much higher potential alcohol content than covered barleys (Agu et al, 2009). Additionally, with advances in brewing technology and mash filters, many brewers no longer require the hull to serve as a filter.…”
mentioning
confidence: 99%
“…At the time of writing there is only one naked barley cultivar on the UK National List: 'Penthouse', listed in 2005(FERA 2011a. However this cultivar was developed for malting, rather than food use, and further developments by Syngenta and the Crisp Malting Group are concentrating on improving the value of naked barley for whisky production (Agu et al 2009). …”
Section: Introductionmentioning
confidence: 99%